Bildende Kunst in Österreich seit 1890. - Bäumer, Angelica (Wien : Bundespressedienst, 1996)
Klimt, Gustav ; Schiele, Egon ; Kokoschka, Oskar ; Frankl, Gerhard ; Mahringer, Anton ; Faistauer, Anton ; Thöny, Wilhelm ; Egger-Lienz, Allan ; Gerstl, Richard ; Kubin, Alfred ; Hauser, Carry ; Birkle, Albert ; Bäumer, Eduard ; Walde, Alfons ; Pauser, Sergius ; Eisenmenger, Hermann Rudolf ; Boeckl, Herbert ; Wotruba, Fritz ; Weiler, Max ; Bilger, Maria ; Moldovan, Kurt ; Lassnig, Maria ; Muthspiel, Agnes ; Hausner, Rudolf ; Fuchs, Ernst ; Lehmden, Anton ; Hundertwasser ; Soucek, Slavi ; Mikl, Josef ; Fruhmann, Johann ; Decleva, Mario ; Staudacher, Hans ; Rainer, Arnulf ; Oberhuber, Oswald ; Frohner, Adolf ; Brus, Günter ; Nitsch, Hermann ; Schwarzkogler, Rudolf ; Lessing, Erich ; Hubmann, Franz ; Export, Valie ; Rühm, Gerhard ; Kandl, Johanna ; Selichar, Günther ; Schlegel, Eva ; Prantl, Karl ; Hrdlicka, Alfred ; Urteil, Andreas ; Hammerstiel, Robert ; Pichler, Walter ; West, Franz ; Kupelwieser, Hans ; Brandstätter, Karl ; Hoke, Giselbert ; Attersee, Christian Ludwig ; Anzinger, Siegfried ; Zobernig, Heimo ; Damisch, Gunter ; Kowanz, Brigitte ; Kogler, Peter ; Ruhm, Constanze ; Sandbichler, Peter
Duits
boek
Keywords: Oostenrijk